Depression and alexithymia effects on emotional eating in people with type 2 diabetes (Annals of Medical Research, 2023)
Aim: Examining the impact of depression and alexithymia related to emotional eating in people with type 2 diabetes is the goal.Materials and Methods: The study included 180 people with type 2 diabetes between the ages of 18 and 65 who applied to the internal medicine outpatient clinic at Malatya Turgut zal University Training and Research Hospital. The patients were given the Toronto Alexithymia Scale (TAS-20), the Dutch Eating Behavior Scale (DEBQ), and the Depression, Anxiety, and Stress Scale (DAS-21).Results: The study's participants had an average age of 44.21 ±11.33 years. The study discovered a significant positive correlation between emotional eating and the challenge of defining stress and emotions (p
Keywords: Emotional eating; Type 2 diabetes; Stress; Depression; Alexithymia